Sew cool [videorecording (DVD)]. - Oedekoven, Kimberly (Learning ZoneXpress, 2010)
Discover how sewing can be SEW cool. Create your own unique look and save some money by learning sewing basics that will give you the skills to make projects all your own. Sewing instructor Kimberly Oekekoven encourages viewers to 'see it, like it, make it' while presenting sewing basics and two easy sewing projects in short segments.